MicroRNA‐574 regulates FAM210A expression and influences pathological cardiac remodeling. Issue 2 (28th December 2020) - Wu, Jiangbin; Venkata Subbaiah, Kadiam C; Jiang, Feng; Hedaya, Omar; Mohan, Amy; Yang, Tingting; Welle, Kevin; Ghaemmaghami, Sina; Tang, Wai Hong Wilson; Small, Eric; Yan, Chen; Yao, Peng
Abstract: Aberrant expression of mitochondrial proteins impairs cardiac function and causes heart disease. The mechanism of regulation of mitochondria encoded protein expression during cardiac disease, however, remains underexplored. Here, we show that multiple pathogenic cardiac stressors induce the expression of miR‐574 guide and passenger strands (miR‐574‐5p/3p) in both humans and mice. miR‐574 knockout mice exhibit severe cardiac disorder under different pathogenic cardiac stresses while miR‐574‐5p/3p mimics that are delivered systematically using nanoparticles reduce cardiac pathogenesis under disease insults. Transcriptomic analysis of miR‐574‐null hearts uncovers family with sequence similarity 210 member A (FAM210A) as a common target mRNA of miR‐574‐5p and miR‐574‐3p. The interactome capture analysis suggests that FAM210A interacts with mitochondrial translation elongation factor EF‐Tu. Manipulating miR‐574‐5p/3p or FAM210A expression changes the protein expression of mitochondrial‐encoded electron transport chain (ETC) genes but not nuclear‐encoded mitochondrial ETC genes in both human AC16 cardiomyocyte cells and miR‐574‐null murine hearts. Together, we discovered that miR‐574 regulates FAM210A expression and modulates mitochondrial‐encoded protein expression, which may influence cardiac remodeling in heart failure. Synopsis: The findings identify that miR‐574 fine‐tunes FAM210A expression and modulates mitochondrial encoded protein expression, thereby maintaining normal mitochondrial function and protecting the heart from cardiac stress induced pathological remodeling. miR‐574‐5p and miR‐574‐3p were induced in failing human and mouse hearts. miR‐574 knockout mice showed severe pathological cardiac remodeling under stress, suggesting a cardioprotective role of miR‐574. Delivery of exogenous miR‐574‐5p/3p mimics antagonized pathological cardiac remodeling. FAM210A interacted with mitochondrial translation elongation factor EF‐Tu and promoted mitochondrial encoded protein expression. miR‐574 fine‐tuned FAM210A expression and modulated mitochondrial encoded protein expression, thereby maintaining normal mitochondrial function. Abstract : The findings identify that miR‐574 fine‐tunes FAM210A expression and modulates mitochondrial encoded protein expression, thereby maintaining normal mitochondrial function and protecting the heart from cardiac stress induced pathological remodeling.